CASE HISTORY OF A TERMINATED CONTRACT. - Allyn, Robert G. (The Accounting Review, 1945)
Abstract The article presents a case history of a terminated, government fixed-price subcontract, it is hoped that someone may profit by another's experience. No suggestion should be read into these facts that this article is offered in a carping or deprecating way. On the contrary, one can only wonder at the stupendous task faced by the administrators of the Contract Settlement Act of 1944 and the perspicacity with which they have handled its very broad provisions. The businessmen of this country can rest easily, at least in respect to the thought that the U.S. Congress and those who have been given authority under the Act have "planned" to "facilitate maximum war production during the war, and to expedite reconversion from war production to civilian production as war conditions permit." The problem of reconversion was not handled quite so expeditiously during and after World War 1. The contract under consideration has only recently been settled, proper names will be omitted. Hereafter, the subcontractor will be referred to as Company X; the prime con-tractor as Company Y, and the contracting governmental agency as Agency Z.